Orchid Exploration in Traditional Forest of Gunung Batuah Gunung Raya District, Kerinci Regency, Jambi - Nursanti Nursanti; Cory Wulan; Emia Anggundary (Jurnal Silva Tropika, 2020)
Orchids are plants that have many types and are spread all over the world. Natural orchids generally grow well in natural forests, especially in mountainous areas. Inventory needs to be done to obtain data and information about the presence of orchid species. This research was conducted in January-February 2017. The research was conducted in Gunung Batuah Traditional Forest, Gunung Raya District, Kerinci Regency, Jambi Province with the method of exploration in the plot at an altitude of 1100 m asl-1400 m asl and 1500 m asl-1650 m asl. The results showed that there were 22 types of orchids found in the research location which were included in 14 genera, where there were 16 types of epiphytic orchids, 4 terrestrial orchids and 3 types of saprophytic orchids. The most common orchids are the genus Bulbophyllum, the genus Liparis and the genus Appendicula. Most individuals are in the type of orchid Bulbophyllum lobbii. Orchids are mostly found at an altitude of 1500 m asl-1650 m asl. The habitat trees that were mostly planted with orchids were Syzigium sp, Litsea Angulata and Vitex heterophylla which were scattered in zone 1 to zone 4. Keywords: Gunung Raya traditional forest, natural forest, orchid